Alternative globalizations : Eastern Europe and the postcolonial world - Mark, James; Kalinovsky, Artemy M.; Marung, Steffi (Bloomington, Indiana : Indiana University Press, Office of Scholarly Publishing, Herman B Wells Library, 2020)
"Globalization has become synonymous with the seemingly unfettered spread of capitalist multinationals, but this focus on the West and western economies ignores the wide variety of globalizing projects that sprang up in the socialist world as a consequence of the end of the European empires. This collection is the first to explore alternative forms of globalization across the socialist world during the Cold War. Gathering the work of established and upcoming scholars of the Soviet Union, Eastern Europe, and China, Alternative Globalizations addresses the new relationships and interconnections which emerged between a decolonizing world in the post-war period and an increasingly internationalist eastern bloc after the death of Stalin. In many cases, the legacies of these former globalizing impulses from the socialist world still exist today. Divided into four sections, the works gathered examine the economic, political, developmental, and cultural aspects of this exchange. In doing so, the authors break new ground in exploring this understudied history of globalization and provide a multifaceted study of an increasing post-war interconnectedness across a socialist world"--
Introduction / James Mark, Artemy M. Kalinovsky, and Steffi Marung -- Part 1. Red globalization? -- The Soviet Union, Eastern Europe, and alternative visions of a global economy 1950s-1980s / James Mark and Yakov Feygin -- The Cold War in the margins of capital : the Soviet Union's introduction to the decolonized world, 1955-1961 / Oscar Sanchez-Sibony -- The Soviet Bloc and China's global opening-up policy during the last years of Mao Zedong / Péter Vámos -- From socialist assistance to national self-interest : Vietnamese labor migration into CMEA countries / Alena K. Alamgir and Christina Schwenkel -- Part 2. A socialist age of development? -- "Socialist development" and East Germany in the Arab Middle East / Massimiliano Trentin -- Entangling agrarian modernities : the "agrarian question" through the eyes of Soviet Africanists / Steffi Marung -- Socialist worldmaking : architecture and global urbanization in the Cold War / Łukasz Stanek -- Part 3. Cultural encounters : discovering similarities, defining difference, creating identities -- Writing the Soviet South into the history of the Cold War and decolonization / Artemy M. Kalinovsky -- Internationalizing the thaw : Soviet orientalists and the contested politics of spiritual solidarity in Asia 1954-1959 / Hanna Jansen -- Soviet antiracism and its discontents : the Cold War years / Maxim Matusevich -- Southeast by Global South : the Balkans, UNESCO, and the Cold War / Bogdan C. Iacob -- Part 4. Global encounter and challenges to state socialism -- A prehistory of postcolonialism in socialist Poland / Adam F. Kola -- Competing solidarities? Solidarność and the Global South during the 1980s / Kim Christiaens and Idesbald Goddeeris -- China is not far! Alternative internationalism and the Tiananmen Square Massacre in East Germany's 1989 / Quinn Slobodian
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
JSTOR
Keywords: Globalization -- Former Soviet republics; Decolonization -- Former Soviet republics; Former Soviet republics -- Foreign relations; Former Soviet republics -- Economic integration; Europe, Eastern -- Foreign relations; Mondialisation -- Ex-URSS.; Décolonisation -- Ex-URSS.; Europe de l'Est -- Relations extérieures.; Ex-URSS -- Relations extérieures.; Ex-URSS -- Intégration économique.; HISTORY -- Europe -- Former Soviet Republics; Decolonization; Diplomatic relations; Globalization; International economic integration; Eastern Europe; Soviet Union -- Former Soviet republics; e-books.; Livres numériques.